The Effect of Good Corporate Governance and Financial Performance on The Corporate Social Responsibility Disclosure of Telecommunication Company in Indonesia - Abriyani, Destya Ramia; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
The company’s annual report is a medium of communication between companies and communities who need financial information and company developments. Currently, not only financial information are taken into consideration for investors, but also information on corporate social responsibility. This study aims to give an idea of corporate social responsibility disclosure in the Indonesian telecommunication sector and to know that the good corporate governance and financial performance with corporate social disclosure in accordance hypotheses simultaneously , while institutional ownership and the audit committee significantly affect the disclosure of corporate social responsibility partially. The next stage is using backward regression analysis method and found that the audit committee is the most influential variable on the disclosure of corporate social responsibility. Keywords: good corporate governance, corporate social responsibility disclosure, firm size, profitability, leverage